Recombinant expression of a truncated Toxoplasma gondii SAG2 surface antigen by the yeast Pichia pastoris - Lau, Y.L.; Fong, M.Y.; Shamilah, R.H.R.; Zulqarnain, M. (2007)
SAG2 is one of the major surface antigens of the intracellular protozoan parasite Toxoplasma gondii. In this study, we used the Pichia pastoris yeast expression system to produce a truncated form of the SAG2 and determined the serological characteristics of this recombinant antigen. We chose the Pichia system because of its high efficiency in expressing recombinant genes, and its ability to modify and secrete the recombinant proteins. Our strategy was to clone and express the part of the SAG2 gene that encodes the carboxyl half of the antigen. The recombinant antigen (recSAG2-C) secreted by the Pichia cells was harvested, and then evaluated in Western blot and enzyme-linked immunoassays (ELISA). Sixty human serum samples, including 45 from confirmed cases of toxoplasmosis, were tested against recSAG2-C. Results from the Western blot assay showed that recSAG2-C reacted with all 45 sera from the toxoplasmosis cases but none with the Toxoplasma-negative serum samples. Similar results were obtained for ELISA. These results indicated that recSAG2-C was specific for Toxoplasma antibody. To investigate the immunological characteristic of recSAG2-C, this recombinant antigen was injected subcutaneously into mice, and their serum was tested against total protein of T. gondii. It was observed that the serum specifically detected the native SAG2 (22 kDa) of T. gondii. This demonstrates that the recSAG2-C could evoke the production of antibody in mice, which readily recognized the native SAG2.